Role of Dexamethasome in Prevention of Post-operative Retching and Vomiting Among Children Undergoing Adeno-Tonsillectomy at Muhimbili National Hospital, Dar Es Salaam, Tanzania (Tanzania Medical Journal, 2015)
Background: Disease in adenoids and tonsils are among the most common problems in paediatrics. Adenotonsillectomy is usually accompanied by significant post operative retching and vomiting. Objective: The aim of the study was to evaluate the role of dexamethasone in prevention of postoperative retching and vomiting (PORV) among paediatric patients undergoing adenotonsillectomy. Methods: This was a single blinded clinical trial study to find out the extent and risk factors of postoperative nausea and vomiting at Muhimbili National Hospital, (MNH.) Results: A total of 94 patients were eligible for the study, the overall proportions of retching and vomiting were 31.91% and 12.77 respectively. More complications of retching and vomiting occurred at the recovery room compared to the ward, which were 30.85% and 8.51% vs. 9.57 and 4.26% respectively. Conclusion: In general patients who received dexamethasone had lower incidence of PORV compared to the controls, however this finding was not statistically significant and did not show to have any effect in the prevention of PORV.